Decision Support Systems with Profile Matching Method in Selection of Achievement Marketing Officer at BRI Katamso Yogyakarta - Wibowo, Ripto Mukti; Permanasari, Adhistya Erna; Hidayah, Indriana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Appreciating outstanding employee by providing reward and recognition is a method to enhance the turnover of the company as well as to motivate the employee’s performance of employees. BRI Katamso constantly encourages the Marketing Officer (MO) to maintain and extent the achievement of targets and performance in order to increase the company's turnover. Pursuing augmentation in turnover and deterioration in MO, BRI has led the ability of MO to be represented to the public. The assessment criteria are set as the MO achievement including: outstanding credit, non-performance loan, Britama achievement, Simpedes attainment, current accounts achievement, deposits achievement, the sum of all achievement, debtors, creditors, the establishment of a blacklist and inclusion on the blacklist. Marketing officers are, in fact, distributed in each BRI Branch Office and numbers of BRI Unit and BRITeras. With the Decision Support System (DSS), it is expected that the computerization system would objectively and precisely assess the MO’s performances. The purpose of this research was to develop SPK in BRI Katamso by applying Profile Matching method.